CRYSTAL ARTHRITIS IN THE DIFFERENTIAL DIAGNOSIS OF NECK PAIN: A CASE OF CROWNED DENS SYNDROME - Halise Hande Gezer; Hamza Özer; Özlem Pehlivan; Mehmet Tuncay Duruöz (Anti-Aging Eastern Europe)
CRYSTAL ARTHRITIS IN THE DIFFERENTIAL DIAGNOSIS OF NECK PAIN: A CASE OF CROWNED DENS SYNDROME